PENGARUH MEREK DAN PEMASARAN GETOK TULAR TERHADAP LOYALITAS KONSUMEN: KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL MODERASI - Malva Nurina Tyagita; Silvana Maulidah; Anisa Aprilia (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
This study discusses the influence of brand trust and 'word of mouth' communication as a marketing strategy on purchasing decisions and consumer loyalty of a packaged chili product. This study conducted an online survey method with purposive sampling technique. Analysis using Structural Equation Modeling. The results showed that the brand trust variable had a direct or indirect effect on consumer loyalty. While the word of mouth variable has an indirect effect on consumer loyalty. The purchase decision variable is used as a mediating variable in the study. The biggest influence is on the brand trust variable and overall the biggest contribution of the indicator is on the company characteristic indicator. Manufacturers need to increase brand trust by improving services and being responsible if there are damaged products and developing word of mouth by marketing products through public figures or influencers on social media.